Regulation of Alternative Sigma Factor Use - Österberg, Sofia; Peso-Santos, Teresa del; Shingler, Victoria (Annual Review of Microbiology, 2011)
Alternative bacterial sigma factors bind the catalytic core RNA polymerase to confer promoter selectivity on the holoenzyme. The different holoenzymes are thus programmed to recognize the distinct promoter classes in the genome to allow coordinated activation of discrete sets of genes needed for adaptive responses. To form the holoenzymes, the different sigma factors must be available to compete for their common substrate (core RNA polymerase). This review highlights (a) the roles of antisigma factors in controlling the availability of alternative sigma factors and (b) the involvement of diverse regulatory molecules that promote the use of alternative sigma factors through subversion of the domineering housekeeping σ70. The latter include the nucleotide alarmone ppGpp and small proteins (DksA, Rsd, and Crl), which directly target the transcriptional machinery to mediate their effects.
Keywords: antisigma factors